Autoriti Hadith Mursal: Satu Perbincangan Mengenai Sikap Imam al-Shafi'i - Ali, Abdul Karim (Jurnal Usuluddin, 1998)
This article endeavours to discuss al-Shafi'i's attitude towards Mursal hadith. As far as Mursal hadith is concerned, scholar shave a different view about it whether it is a decisive proof (hujjah) or not in Islam. So, al-Shafi'i as a well known scholar in jurisprudence and hadith, we attempt to elaborate his own view on this issue as well as other scholars' view on his attitude towards Mursal hadith.